Expressive speech acts during disasters: A pragmatic analysis of the Aceh tsunami oral history archive - Faisal Faisal; Anang Santaso; Gatut Susanto; Martutik Martutik; Siti Naila Fauzia (Studies in English Language and Education, 2025)
The Aceh Tsunami Oral History archive transcribes firsthand accounts from survivors of the December 26, 2004, tsunami, capturing their experiences as direct witnesses to the disaster. These narratives express emotions such as anxiety, panic, worry, distress, and disorientation. This frame of mind reflects the psychological turmoil faced during the earthquake and tsunami waves. This study focuses on expressive speech acts (ESAs), aiming to identify their types, strategies, and patterns in the oral history archive. A qualitative pragmatic approach was employed, with data collected through reading, recording, coding, tabulating, and categorizing. The process of data analysis followed five stages: description, selection, analysis, interpretation, and conclusion. The findings reveal that Aceh tsunami survivors used 22 types of ESAs, both direct and indirect. A number of 65 strategy patterns emerged from two primary strategies, shaping communication based on the survivors intended interlocutors. The expressions directed toward Allah, the one God, were dominant, featuring religious language and strong Islamic references. The use of hadih maja (Acehnese proverbs) was also identified, illustrating how the survivors speech acts integrate cultural and religious elements in their communication. The findings have inclusively presented the deep interconnection between faith, Acehnese cultural wisdom, and the ESAs of tsunami survivors.